One Health: Why livestock matter - International Livestock Research Institute (International Livestock Research Institute, 2021)
One Health acknowledges that the health of animals, humans and the environment are intrinsically linked. The livestock sector plays an essential role in tackling interconnected One Health challenges such as zoonotic diseases and antimicrobial resistance.